The Application of Restorative Justice in Civil Dispute Resolution: Potentials and Challenges in Indonesia - Halim, Abdul (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this study is to assist the community in handling cases. Settlement of civil disputes can be carried out through a trial process in court. The research method uses a descriptive qualitative research approach, namely research on natural objects from experiments. with observational data collection techniques, interviews. The results of the research description of the application of Restorative Justice in Indonesia are still limited and face various challenges, such as a lack of public understanding of the concept of Restorative Justice, limited resources, and a lack of support and coordination between institutions. The findings contribute to a deeper understanding of the possibilities and obstacles involved in integrating restorative justice approaches into the civil justice system in Indonesia. Recognized by society and the judiciary. There are challenges in the implementation of restorative justice, such as the lack of trained human resources and adequate facilities, so that improvements and development are needed so that restorative justice can be implemented properly.